Incentive policies for residential buildings energy retrofit. An analysis of tax rebate programs in Italy. - Bonifaci, Pietro; Copiello, Sergio (Springer, 2018)
Starting from the oil crisis that occurred in the early 1970s, the issue of energy efficiency has occupied an ever more prominent place in the economic, political, and academic debate. In this context, the construction industry has been considered among the sectors that have the greatest potential for the reduction of energy consumption and greenhouse gas emissions, as well as for the use of energy from renewable sources. With regard to the European situation that is the focus of this research, the first regulations on building energy performances date back to the mid-seventies. These regulations, which had a significant spread until the 1980s, have focused on the definition of minimum requirements for the building elements. Over the years, the introduction of new regulations has established a series of economic instruments for the promotion of energy-saving technologies. During the last decade, the use of incentive programs has strengthened. Meanwhile, what has been gradually better recognized is the role played by the refurbishment of existing buildings in reducing energy consumption and greenhouse gas emissions, as stressed by the most recent Directive 2010/31/EU on the energy performance of buildings. Under this framework, the incentive policies intended to achieve energy improvements in buildings face a twofold challenge. On the one hand, they have to stimulate the increase of the rate of building renovation; on the other, they should ensure the achievement of minimum performance standards, according to the EU's goals. Given these premises, this research aims to verify, using a Discounted Cash Flow Analysis, the suitability of the tax rebates currently in force in Italy to stimulate private investments and to be an effective tool to reduce the EU's energy consumption. The investment costs of 14 refurbishment alternatives, applied to seven single-family houses located in Italy, are estimated. The cost appraisal considers the retrofit expenses and all the ancillary costs that affect the decision-making process of a private investor, as well as the effect of the tax rebates. The results we achieve underline that the analyzed programs are not completely able to stimulate the enhancement of minimum energy standards in buildings. Indeed, the maximum amount of works eligible for the deduction is too high, if linked to an actual increase in global energy performance. This mechanism makes more profitable the exploitation of incentives related to the adoption of specific technologies, which, however, do not guarantee the overall increase of the buildings' performances.
Keywords: Energiepolitik; Bauindustrie; Gebäudesanierung; Energieverbrauch; Erneuerbare Energie; Energieeinsparung; Energetische Sanierung; Energieeffizienz; Treibhausgas; Investition; Wertermittlung; Entscheidungstheorie